Positive, Mildly Positive, and Uncertain Nasopharyngeal Swab and Outcome in COVID-19 Patients. Issue 1 (22nd January 2022) - Malerba, Paolo; Boari, Gianluca E. M.; Nardin, Matteo; Tomasi, Cesare; Chiarini, Giulia; Bonetti, Silvia; Bianco, Gianluca; Faustini, Cristina; Braglia-Orlandini, Federico; De Ciuceis, Carolina; Rizzoni, Damiano
Abstract : Introduction and Aim: Diagnosis of SARS-CoV-2 infection is mainly based on gene detection through polymerase chain reaction analysis on nasopharyngeal swab. The Allplex TM 2019-nCoV assay targets 3 different viral genes: RNA-dependent RNA polymerase, envelope, and nucleocapside. A coding system was developed based on different number of genes expressed: a nasopharyngeal swab was considered "positive" if all 3 genes tested underwent amplification, "mildly positive" if only 2 out of 3 genes were detected, "uncertain" if only 1 gene and "negative" if none resulted amplified from the test. Our aim was to assess whether this classification correlates with clinical outcome in a cohort of COVID-19 patients. Methods: This is a retrospective study including patients admitted with diagnosis of SARS-CoV-2 infection to a medical ward at the Montichiari Hospital, Brescia, Italy, from February 28 to April 30, 2020. All patients underwent the nasopharyngeal swab upon admission. Results: A total of 204 patients were included in this study. Patients with full positive nasopharyngeal swab showed higher values of C-reactive protein and neutrophiles/lymphocytes ratio compared with patients with mildly positive or uncertain nasopharyngeal swab. Mortality did not differ between the 2 groups. A Cox multivariate analysis showed that age, male sex, and CRP values are independent predictors of in-hospital mortality. Conclusions: Our study demonstrated that patients with a complete SARS-CoV-2 gene detection nasopharyngeal swab show a higher inflammatory profile, and this can be an indirect measurement of viral load in COVID-19 patients.